bạn cứ nhân lên hợp cho từng cái 1 là ra đó mà
Đơn giản thế này thôi nhé : ^^
Xét với n > 0 : \(\frac{1}{\sqrt{n}+\sqrt{n+1}}=\frac{\sqrt{n+1}-\sqrt{n}}{\left(\sqrt{n+1}-\sqrt{n}\right)\left(\sqrt{n+1}+\sqrt{n}\right)}=\frac{\sqrt{n+1}-\sqrt{n}}{\left(n+1\right)-n}=\sqrt{n+1}-\sqrt{n}\)
Áp dụng : \(\frac{1}{\sqrt{1}+\sqrt{2}}+\frac{1}{\sqrt{2}+\sqrt{3}}+...+\frac{1}{\sqrt{24}+\sqrt{25}}=\sqrt{2}-\sqrt{1}+\sqrt{3}-\sqrt{2}+...+\sqrt{25}-\sqrt{24}\)\(=-1+\sqrt{25}=5-1=4\)
Câu b) bạn làm tương tự nhé ^^